Effects of pH on protein components of extracted oil bodies from diverse plant seeds and endogenous protease-induced oleosin hydrolysis. (1st June 2016) - Zhao, Luping; Chen, Yeming; Chen, Yajing; Kong, Xiangzhen; Hua, Yufei
Highlights: Many extrinsic proteins are present in pH 6.5-extracted oil bodies. Extrinsic proteins primarily include globulins, 2S albumins, and enzymes. These extrinsic proteins showed different resistances to extraction pH. Proteases of oleosins are already bioactive in all selected plant seeds. Abstract: Plant seeds are used to extract oil bodies for diverse applications, but oil bodies extracted at different pH values exhibit different properties. Jicama, sunflower, peanut, castor bean, rapeseed, and sesame were selected to examine the effects of pH (6.5–11.0) on the protein components of oil bodies and the oleosin hydrolysis in pH 6.5-extracted oil bodies. In addition to oleosins, many extrinsic proteins (globulins, 2S albumin, and enzymes) were present in pH 6.5-extracted oil bodies. Globulins were mostly removed at pH 8.0, whereas 2S albumins were removed at pH 11.0. At pH 11.0, highly purified oil bodies were obtained from jicama, sunflower, peanut, and sesame, whereas lipase remained in the castor bean oil bodies and many enzymes in the rapeseed oil bodies. Endogenous protease-induced hydrolysis of oleosins occurred in all selected plant seeds. Oleosins with larger sizes were hydrolysed more quickly than oleosins with smaller sizes in each plant seed.